Effect of Clothing Fabric Color on UV Ray Absorption Efforts to Protect the Skin - Purwito Soegeng asetijono; Andhika Dwi Anggara; Nila Prasetya Aryani (Syntax Corporation Indonesia, 2023)
Despite the many benefits of sunlight, it can also have negative impacts on our health, particularly from Ultraviolet (UV) radiation. To reduce the risks, one can protect themselves by wearing appropriate clothing, avoiding prolonged exposure to sunlight, especially Ultraviolet (UV) radiation. It is necessary to pay attention to the choice of clothing colors considering that each color actually absorbs sunlight with different abilities. Therefore it is very important for us to know the color selection of clothes to wear in reducing exposure to UV rays on our skin. The objective of this study is to determine the difference in the effect of clothing fabric color on UV ray absorption. The UV intensity data obtained is the intensity of UV that has passed through a cloth filter with a certain color and the intensity without a filter. Data collection was conducted with 10 different cloth color variations. The results will be compared between the UV intensity with various colored cloth filters and the intensity without a filter. It was found that different colors on fabric also affect the intensity of UV rays that are absorbed or transmitted. Relatively bright colors will cause a dominant amount of UV rays to pass through compared to dark-colored fabrics. The fabric colors that allow more UV radiation to pass through are those that are predominantly light, in this study, the colors Purple and White.